PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PT ADHI KARYA (PERSERO) TBK PERIODE 2013-2022 - Agustina, Anita; Sutiman (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the Current Ratio (CR) and Debt to Equity Ratio (DER) on share prices at PT Adhi Karya (Persero) Tbk for the 2013-2022 period, both partially and simultaneously. The type of research used is quantitative research, and is descriptive. The data collection technique used is published secondary data, data taken from the official website of PT Adhi Karya (Persero) Tbk for the 2013-2022 period. The data analysis method used in this research is descriptive statistics, classical assumption testing, and also uses simple and multiple linear regression data analysis techniques, correlation coefficient, hypothesis testing (t test and f test), and coefficient of determination. From the results of hypothesis testing, the t test shows that the Current Ratio (CR) has no significant effect on share prices, where the t value is 1,420 < t table value 2.365, with a significance value of 0.277 < 0.05, while the Debt to Equity Ratio (DER) has a significant effect on stock prices. where the tcount value is 2,757 > ttable value 2.365, with a significance value of 0.028 < 0.05. Simultaneously (F test) Current Ratio (CR) and Debt to Equity Ratio (DER) together have no significant effect on share prices where the calculated F value is 4,079 > Ftable value 4.74 with a significance of 0.067 > 0.05. The coefficient of determination test shows a value of 53.8%, while the remaining 46.2% is influenced by other variables not examined in this research.